2000
DOI: 10.1002/hep.510310106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a locally driven mucosal response and the presence of mitochondrial antigens in saliva in primary biliary cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is often considered to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 33 publications
7
41
0
Order By: Relevance
“…These data and the recent evidence of the presence of IgG and IgA AMA in the saliva of PBC patients 24 together support the earlier observation and hypothesis that a PDC-E2 molecule might be aberrantly expressed in the salivary glands of PBC patients, and the possible association of Sjö gren's syndrome with PBC. 23 In a previous study, the V, D, and J segment utilization in XenoMouse animals was shown to be nearly identical to the gene segment utilization reported for humans.…”
Section: Discussionsupporting
confidence: 89%
“…These data and the recent evidence of the presence of IgG and IgA AMA in the saliva of PBC patients 24 together support the earlier observation and hypothesis that a PDC-E2 molecule might be aberrantly expressed in the salivary glands of PBC patients, and the possible association of Sjö gren's syndrome with PBC. 23 In a previous study, the V, D, and J segment utilization in XenoMouse animals was shown to be nearly identical to the gene segment utilization reported for humans.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that these differences reflect a much higher titer of autoantibodies to PDC-E2 compared to OGDC-E2 or BCOADC-E2 not only in the sera, but also in the secretions in PBC. 7,8,42,43 It would be interesting to prospectively study patients ranked on their capacity to induce caspase activation in this system and determine whether this predicts their progression of disease. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…111 Further, the PDC-E2 amino acids E, D, and K are essential for the recognition of the epitope by HLA-restricted T-cell clones, similar to that observed for AMA. PDC-E2 [163][164][165][166][167][168][169][170][171][172][173][174][175][176] -specific CD4 þ Tcell clones also react with other AMA-specific mitochondrial autoantigens, including the E2 subunits of OGDC and BCOADC, as well as E3BP. 112,113 In all these molecules, interestingly, the epitopes include a lipoylated domain.…”
Section: Immunopathogenesis Of Pbcmentioning
confidence: 99%
“…The study of TCR b gene rearrangements of cell clones obtained from PBC liver biopsies demonstrated different degrees of oligoclonality of the infiltrating T cells. 114,115 The use of TCR Vb or Jb genes by PDC-E2 [163][164][165][166][167][168][169][170][171][172][173][174][175][176] -reactive T-cell clones is also highly diverse with GXG or GXS motifs found within the complementaritydetermining region 3 (CDR3) of all T-cell clones. 116 When autoreactive T-cell frequencies are compared among different tissues of patients with PBC, PDC-E2 163-176 -reactive precursor T cells are 100-150-fold more represented in the hilar lymph nodes and the liver compared to the peripheral blood, possibly with changes in different disease stages.…”
Section: Immunopathogenesis Of Pbcmentioning
confidence: 99%